Mouse adaptation of H6 avian influenza viruses and their molecular characteristics - Wan, Zhimin; Gong, Jianxi; Sang, Jianjun; Jiang, Wenjie; Zhao, Zhehong; Lian, Mingjun; Tang, Ting; Li, Yafeng; Kan, Qiuqi; Xie, Quan; Li, Tuofan; Shao, Hongxia; et al. (Frontiers in Microbiology, 2022)
H6 avian influenza viruses (AIVs) not only continue to circulate in both domestic poultry and wild waterfowl, but also have occasionally caused spillovers infections in pigs and humans, posing a potential threat to public health. However, the molecular mechanism of H6 AIV adaptation to mammals remains largely unknown. In this study, two mouse-adapted (MA) H6 AIV strains, named as MA E-Teal/417 and MA GWF-Goose/740, were generated through blind passages in BALB/c mice. The two MA H6 strains replicated more efficiently and showed higher virulence than the corresponding wild type (WT) H6 strains in mice. Genome sequencing revealed that MA E-Teal/417 and MA GWF-Goose/740 carried six amino acid mutations (PB2-T224A/E627K, HA-G124R, NA-F167L/Y356H and M1-M92R), and four amino acid mutations (PB1-K577E, PA-T97I/D514E and HA-T276K), respectively, when compared to the corresponding WT virus. Receptor binding assay showed MA E-Teal/417 had stronger binding activity to α-2,3 SA than WT E-Teal/417. Moreover, the polymerase activity analysis found the RNP polymerase activity of both MA H6 viruses was significantly higher than that of the corresponding WT virus in 293T cells. All these demonstrate that H6 AIV can acquire limit amino acid substitutions to adapt to mammals and increase virulence, highlighting the significance of monitoring such mutations of H6 AIV in the field for alarming the potential of its cross-transmission and pathogenesis in mammals.